PHYSIOLOGICAL ASPECTS OF THE DEVELOPMENT OF INDIVIDUAL VALEOLOGICAL COMPETENCES - Kholliyeva, Shakhlo (International Conference on Business & Management, 2025)
This article analyzes the role of physiological factors in the formation and development of valeological competencies of a person, their place and significance in the educational process from a scientific and pedagogical point of view. Valeology, as a science aimed at studying human health, life activities and a healthy lifestyle, serves to form a culture of healthy living in students and pupils. The article extensively covers the healthy psychophysiological development of a person, the characteristics of the body’s activity in the younger periods, the influence of stress and emotional states, and the role of pedagogical and psychological approaches in the development of valeological competencies.